Comportamento ingestivo de vacas jersey em lactação, manejadas em diferentes pastagens no período hibernal - Carneiro, Juliane (2011)
This study aimed to evaluate the ingestive behavior (grazing, ruminating and resting) of Jersey cows in milk, in pasture managed tropical estrela africana (Cynodon nlemfuensis) sobressemeadas azevém (Lolium multiflorum Lam) in winter period. The experiment was conducted at the Unidade de Ensino e Pesquisa de Bovinocultura de Leite, localizada na Universidade Tecnológica Federal do Paraná- UTFPR, Câmpus The area used was 1,200 square meters, divided into two paddocks. We used six Jersey cows. The parameters evaluated were: time spent on pasture (P), time spent ruminating (R) and leisure (O) for each grazing cycle of 10 hours of evaluation. The percentage of grazing time in different times and on different forage systems presented statistical difference (P <0.05). The grazing time in the month of July did not differ from other periods; the time of cows grazing in the month of August was higher than the time for collection of fodder in September. Regarding the length of the grazing animal, grazing estrela africana was greater than the residence time of the animals when compared to the system sobressemeado forage azevém (P <0.05). The percentage of leisure time as a function of the grazing period showed no statistical difference (P <0.05). Regarding the percentage of idle systems to feed the animals remained idle in the most azevém sobressemeado pasture in relation to the system only estrela africana. The rumination of cows remained in paddocks with azevém sobressemeado was higher than that of animals that remained in estrela africana pickets (P <0.05). The rumination in the month of September was higher than the grazing cycles of the months of July and August. The sobressemeadura azevém was superior in relation to estrela africana system is thus an important alternative to be used during the winter period.